New records of long-legged flies (Diptera, Dolichopodidae) from Novosibirsk Region of Russia - Grichanov, I. Ya.; Kosterin, O. E.; Ahmadi, A. (Acta Biologica Sibirica, 2017)
During a 2017 survey conducted in the Novosibirsk Region of Russia, about 600 specimens of Dolichopodidae were collected. Almost all 44 identified species are recorded for the first time in the Novosibirsk Region.